Retrograde intussusception post Roux-en-y gastric bypass - Rockliff, Aaron (J Surg Case Rep, 2021)
A 72-year-old female presented to the emergency department with a short history of abdominal pain and vomiting, having undergone laparoscopic Roux-en-y gastric bypass (RYGBP) 3 years earlier. Computed tomography imaging revealed intussusception causing small bowel obstruction, so she was taken emergently to theatre. Intra-operative findings were of a retrograde intussusception at the jejunojejunostomy. Retrograde intussusception in patients post RYGBP has a unique pathophysiology and management.